KOORDINASI KERJA ANTARA RECEPTIONIST DENGAN ORDER TAKER DALAM MEMPERSIAPKAN PENJUALAN KAMAR DI HOTEL TJOKRO PEKANBARU - Eriadi, Rosi; Yusrizal, Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research aims to determine the coordination system of work between receptionists and order takers in preparing room sales at Tjokro Pekanbaru Hotel. Coordination is the process of integrating activities that aim to produce an action to achieve a common goal in an organization.This research uses qualitative methods to examine the problems studied by making key informants as many as six people as resource persons, namely one Front Office Manager, one Housekeeping Manager, two Order Takers, two Receptionist people. While the data collection techniques in this study used observation, interviews and documentation.Based on the results of the research that has been done, for the whole of the results of the interview answers said that the coordination of work between Receptionist and Order Taker is sufficiently implemented, but still needs to be improved.Keywords : Coordination, Receptionist, Order Taker